Financial Distress Prediction In Asean Islamic Banks Using The Altman, Springate, And Grover Models : Financial Distress Prediction In Asean Islamic Banks Using The Altman, Springate, And Grover Models - muhammad faizal assyiddiq; Ersi Sisdianto; Sania Nuraziza (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2026)
This study aims to evaluate and compare the financial health levels of Islamic banks in the ASEAN region using the Altman, Springate, and Grover models. Amid the dynamics of the regional economy, risk assessment through multivariate models becomes crucial as an early detection instrument for stakeholders. By taking samples from BCAS, BIMB, BIBD, and iBank for the 2020-2024 period, the results show that all sampled banks are classified as financially healthy based on the Grover model. These findings indicate a strong financial resilience within the Islamic banking sector in ASEAN, while also highlighting variations in accuracy among the models in classifying firms’ financial conditions